2004
DOI: 10.1021/cm035014t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Surface Chemistry of Spherical Mesoporous Organic−Inorganic Hybrid Particles with an Integrated Alcohol Functionality on the Pore Surface

Abstract: Novel mesoporous organic−inorganic spherical hybrid particles are described that contain a 3-hydroxypropyl organic functionality which is integral to the pore surface. The 3-hydroxypropyl hybrid particle is synthesized in three steps starting from a 4:1 (mol/mol) mixture of tetraethoxysilane and [3-(methacryloxy)propyl]trimethoxysilane, where the monomers are polymerized to a poly(organoalkoxysilane) oil, followed by sol−gel reaction to the hybrid silicate bead, which is finally subjected to an alkaline hydrot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Peaks are relatively broad attributed to the restricted mobility of the functional groups attached to the surface of SBA-15 [34]. After a simple addition reaction between amino groups and glycidol, three new resonance peaks at 51.2, 64.2 and 71.9 ppm appear, which are assigned to d, f, and e position carbons [35] as shown in Fig. 1B, respectively.…”
Section: Resultsmentioning
confidence: 93%
“…Peaks are relatively broad attributed to the restricted mobility of the functional groups attached to the surface of SBA-15 [34]. After a simple addition reaction between amino groups and glycidol, three new resonance peaks at 51.2, 64.2 and 71.9 ppm appear, which are assigned to d, f, and e position carbons [35] as shown in Fig. 1B, respectively.…”
Section: Resultsmentioning
confidence: 93%
“…21 A variety of aminoalkyl(trialkoxy)silanes are commercially available and have been widely used for surface modification, while more chain structures have been pursued. The attachment of amines on modified mesoporous silicas, [23][24][25][26][27][28][29] summarized in Scheme 2, has been widely studied. These aminofunctionalized mesoporous silicas have been used for base catalysts and cation traps.…”
Section: Silane Synthesis In Advance Vs On-surface Synthesis (Also Camentioning
confidence: 99%
“…31 Ding et al reported the conversion of terminal alcoholic OH on a mesoporous silica (2R p = 10 nm, not in a periodic structure) surface into a variety of organic groups. 32 They carried out an elemental analysis to evaluate the degree of transformation and hence the level of new substituent derivatization, which are summarized in Figure 2. All surface compounds showed clear resonances in the 13 C-NMR spectra, accompanied by peaks due to unreacted HOCH 2 CH 2 CH 2 -chains.…”
Section: Silane Synthesis In Advance Vs On-surface Synthesis (Also Camentioning
confidence: 99%
“…Polymer-coated [16], horizontally polymerized [17,18], bidentate [5,13] and polar embedded stationary phases are typical examples. In recent years, a unique class of organic/inorganic hybrid silica materials have been developed, which is normally prepared by condensing alkoxysiloxanes with monosubstituted XSi(OR) 3 or organic-bridged (R O) 3 SiRSi(OR ) 3 [19][20][21][22]. Compared with inorganic silica materials, the columns packed with hybrid materials have increased chemical stability toward a broader pH range [15,19,22].…”
Section: Introductionmentioning
confidence: 99%